2017
DOI: 10.1097/aog.0000000000002093
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Opioid Prescription and Use After Cesarean Delivery

Abstract: Objective To define the amount of opioid analgesics prescribed and consumed after discharge after cesarean delivery. Methods We conducted a survey at six academic medical centers in the United States from 9/2014 to 3/2016. Women who had undergone a cesarean delivery were contacted by phone two weeks after discharge and participated in a structured interview about the opioid prescription they received upon discharge and their oral opioid intake while at home. Results A total of 720 women were enrolled; of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
193
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(203 citation statements)
references
References 13 publications
(13 reference statements)
6
193
2
2
Order By: Relevance
“…However, recent studies found no association between the amount of opioid prescribed and the likelihood of refill request after surgery 20 , and no association between the initial postoperative prescription, patient satisfaction 8 , or the Hospital Consumer Assessment of Healthcare Providers and Systems pain measure. 21 These findings should reassure surgeons that reducing the amount of opioid provided after surgery should still provide adequate pain management while maintaining patient satisfaction in most patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, recent studies found no association between the amount of opioid prescribed and the likelihood of refill request after surgery 20 , and no association between the initial postoperative prescription, patient satisfaction 8 , or the Hospital Consumer Assessment of Healthcare Providers and Systems pain measure. 21 These findings should reassure surgeons that reducing the amount of opioid provided after surgery should still provide adequate pain management while maintaining patient satisfaction in most patients.…”
Section: Discussionmentioning
confidence: 96%
“…8,9 However, few studies have examined whether individual patient factors predict outpatient opioid use. One recent study reported that individual in-hospital opioid consumption was correlated with post-discharge opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most women (95.3%) did not dispose of their leftover medications. 3 One study reported that 4.7% of pregnant women reported using an illicit substance in the past month. 4 One study reported that 1 in 300 women will become dependent on opioids after a cesarean delivery.…”
Section: Epidemiology Of Opioid Use In Pregnancymentioning
confidence: 99%
“…This project is the first to suggest a difference in postoperative opioid requirements between patients undergoing primary versus repeat CD. With regard to opioid administration, medical practitioners often prescribe opioids as part of their multimodal analgesic regimen to control postoperative pain after CD [16]. For this study all patients received multi-modal strategies for postoperative pain control, and none received additional regional procedures such as transverse abdominis plane block outside of the spinal anesthetic.…”
Section: Discussionmentioning
confidence: 99%